Components and Antimicrobial Activity of Polysaccharides Extracted from Thai Brown Seaweeds - Attachai Kantachumpoo; Anong Chirapart (Agriculture and Natural Resources, 2010)
Seven species of brown seaweed, Colpomenia sinuosa (CS), Hydroclathrus clathratus (HC), Dictyota dichotoma (DD), Padina australis (PA), P. minor (PM), Sargassum polycystum (SP) and Turbinaria conoides (TC) were collected from Chon Buri (01), Chumphon (02) and Rayong (03) provinces. Polysaccharides were extracted by boiling the dried seaweed samples in water at 100°C (E1) for 2 h and at 75°C, adjusted to pH 3 by addition of 2 mol/l HCl (E2), for 5 h. The total polysaccharide yield, total carbohydrate, sulfate content and sugar components of the E1- and E2-extracts were determined. The E1-extract of SP03 gave a maximum yield of 1.97±1.15% (w/w). The greatest percentage of carbohydrate (55.95±0.72%) was obtained from the E1-extract of PM02. The maximum sulfate content (18.10±0.25%, w/w) was obtained from HC01. For the E2 extraction, the maximum yield (19.69±0.23%, w/w) was obtained from HC01, while the greatest percentage of total carbohydrate obtained was 44.41±0.94% (w/w) in PM02. The sulfate content was high in the E2-extract from CS01 (14.22±0.69%). Fucose was identified as a main component in all extracts, with the highest percentage in HC01 (12.35%). Mannose was observed in samples from CS01, PA03, PM02, SP01 and SP03, but not from DD02, HC01, PA01 PA02 or TC02. Furthermore, regarding the antimicrobial activity determined in both extracts at 2 mg/ml, only the E1- and E2-extracts of SP01 and the E2-extract of CS01 demonstrated activity against Candida albicans. In contrast, most of the E1- and E2-extracts were not only inactive against the microorganisms that were tested, but actually promoted microbial growth, particularly in the case of extracts that contained mannose.